Value of dysmorphic red cells and G1 cells by phase contrast microscopy in the diagnosis of glomerular diseases (Mymensingh Medical Journal, 2011)
Mymensingh Med J. 2011 Jan;20(1):71-77 The abstract of this article is available on the PubMed website